2012
DOI: 10.1093/cid/cis842
|View full text |Cite
|
Sign up to set email alerts
|

Defective Pneumococcal-Specific Th1 Responses in HIV-Infected Adults Precedes a Loss of Control of Pneumococcal Colonization

Abstract: These data reveal the persistently poor control of pneumococcal colonization in HIV-infected adults following immune ART-mediated reconstitution, highlighting a potential reservoir for person-to-person spread and vaccine escape. Novel approaches to control colonization either through vaccination or through improvements in the quality of immune reconstitution are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
57
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 44 publications
(69 reference statements)
10
57
1
Order By: Relevance
“…Moreover, despite few studies describing higher levels of isotype switched B cells in treated patients compared to naive [27] and differentiate from HIV negative individuals [28], our study confirmed more recent authors [29], underlining the need for further investigation on this specific memory subset.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, despite few studies describing higher levels of isotype switched B cells in treated patients compared to naive [27] and differentiate from HIV negative individuals [28], our study confirmed more recent authors [29], underlining the need for further investigation on this specific memory subset.…”
Section: Discussionsupporting
confidence: 85%
“…NK cells, the main producers of IFN-γ, were previously shown to be less responsive to ex vivo stimulation with E. coli or NTS in HIV-positive patients [18]. Furthermore, IFN-γ production in response to pneumococcal antigens was reduced in CD4 T cells from HIV patients [19]. Our findings extend the relevance of these findings to a whole blood stimulation model and a wider range of bacterial agonists.…”
Section: Discussionsupporting
confidence: 78%
“…HIV infected adults in our setting have higher rates of pneumococcal carriage than HIV uninfected individuals [Kamng’ona et al 2013 unpublished]. The high rates of bacterial meningitis in HIV positive adults may be potentially related to increased susceptibility to S.pneumoniae infection via altered mucosal and cell-mediated immunity [28]. Immunocompromise has been associated with ABM in adults, but HIV has not to date been proven to be an independent risk factor [9], [23], [24], [29].…”
Section: Discussionmentioning
confidence: 99%